One Hundred Two Consecutive Hepatobiliary Resections for Perihilar Cholangiocarcinoma With Zero Mortality - Sano, Tsuyoshi (2006)
OBJECTIVE: To analyze the short-term surgical outcome of hepatobiliary resections for perihilar cholangiocarcinoma in the last 5 years. SUMMARY BACKGROUND DATA: Hepatobiliary resection for perihilar cholangiocarcinoma remains a technically demanding procedure, calling for a high level of expertise in biliary and hepatic surgery, and is still associated with significant morbidity or mortality. METHODS: Between 2000 and 2004, we surgically treated 102 consecutive patients with perihilar cholangiocarcinoma with a management strategy consisting of preoperative biliary drainage, portal vein embolization (for right-sided and extended left-sided resections), and major hepatobiliary resection. The data on all of the patients were analyzed retrospectively to identify the factors that might significantly affect the postoperative mortality and morbidity. RESULTS: There were no cases of in-hospital mortality or postoperative liver failure. Major complications were encountered in 7 patients (6.9%), and the overall morbidity rate was 50%. Reoperation was required in 2 patients (2%). The overall median length of postoperative hospital stay was 26 days (range, 13–119 days). Univariate analysis in relation to the postoperative morbidity showed significant differences in the preoperative occurrence of segmental cholangitis or cholecystitis (P = 0.015), the severity of postoperative hyperbilirubinemia (P < 0.001), and the total amount of fresh frozen plasma administered (P = 0.002). Multivariate analysis revealed a single independent significant predictive factor for postoperative morbidity, namely, preoperative cholangitis or cholecystitis (odds ratio, 9.08; 95% confidence interval, 1.05–78.56, P = 0.045). CONCLUSIONS: Our experience indicates that hepatobiliary resections for perihilar cholangiocarcinoma can be conducted safely, without a single case of postoperative liver failure or mortality. Occurrence of preoperative cholangitis or cholecystitis is a significant indicator for morbidity of major hepatobiliary resection.